Collective action and social change: examining the role of representation in the communication between protesters and third-party members - Batel, S.; Castro, P. (Journal of Community and Applied Social Psychology, 2015)
Within social psychology, it has been proposed that to understand how collective action creates social change, it is relevant to examine the role that other members of society can have on it. However, few studies have empirically examined that. We argue that for that task, it is useful, first, and as some authors have already argued, to go beyond the sole analysis of the two-sided inter-group relations creating collective action; and second, to articulate this with contributions from social representations theory, which recognises that to understand social change, we need to examine communicative practices, or how communication is used between collective action's actors and other actors to re-present identities. We analyse the protests by a movement of residents from a Lisbon neighbourhood that protested against the transformation of a neighbourhood's convent. Besides discussing this transformation with local authorities and failing to achieve its aims through that, the protesters also discussed it with other citizens. The analysis of this debate shows that the arguments and actions they used change throughout time, from local to global, as the latter were the ones more endorsed by other citizens and thus those that could help the protesters to achieve their goals